Near-Infrared Based Real-Time Peripheral Superficies Venous Imaging Solution for Difficult Venous Access - Gopalakrishnan, Dr. S. (International journal of recent technology and engineering, 2019)
The proposed solution, the vein viewer provides a reliable solution for patients having Difficult Venous Access (DVA). DVA is a medical condition wherein the superficial veins are not easily palpable because of skin tone, obesity or age. The lack of visualization of veins results in wrong site of venepuncture and this can lead to many potential risks. The proposed model is based on the Near- Infrared (NIR) Technology to view the vein pattern which is not visible when seen by normal human eye. The infrared radiations illuminate the subject's hand and the image is captured using CMOS sensor with no IR cut lens. The captured image is preprocessed and image processing algorithms are performed to enhance the vein pattern. The processed image is then displayed real- time on a Liquid Crystal Display (LCD). The components are cased to form a single unit so that it can be handheld or mounted so that the practioner's hands are free for easily placing the needle. The cost of the product is greatly reduced so as to make this technology widely acceptable.